LAPAROTOMY FOR PERITONITIS: PRIMARY OR DELAYED PRIMARY CLOSURE? - Nasib, Gul; Shah, Syed Inamullah; Bashir, Eitezaaz (Journal of Ayub Medical College Abbottabad, 2015)
Background: Although literature does not provide a level-1 evidence to support either method of closure, various studies have shown a reduced frequency of superficial surgical site infection with delayed primary closure (DPC) as opposed to primary closure (PC). Nevertheless, PC is still preferred by most surgeons to avoid a second procedure. This study was conducted with the objective to compare the frequency of wound infection and duration of hospitalization among patients undergoing primary and delayed primary closure of the skin wound following laparotomy for peritonitis. Methods: A randomized controlled trial comprising 70 patients: Thirty-five patients underwent PC (Group-A) and 35 DPC (Group-B). Frequency of wound infection during follow up period and duration of hospital stay was noted in both groups. Results: In group-A, 18 (51.43%) patients showed wound infection while in group-B, it was 9 (25.71%) with p=0.027. Mean hospital stay recorded in group-A was 7.03 days±1.81, and for group-B, it was 6.34 days±4.14 (p=0.372). Conclusion: DPC for surgical wounds is better than PC technique as it decreases the frequency of wound infection during follow-up period without any significant increase in duration of hospital stay.